2014
DOI: 10.1682/jrrd.2014.02.0045
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury combined with felony history: Effect on supported employment for Veterans

Abstract: Abstract-In this secondary analysis of data from a randomized controlled trial comparing supported employment with treatment as usual, we sought to evaluate the study incident rate of legal involvement and subsequent effects of legal involvement on employment among 157 job-seeking Veterans with spinal cord injury. The supported employment vocational rehabilitation program, called the Spinal Cord Injury-Vocational Integration Program, adhered as closely as possible to principles of supported employment as devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Vocational training was the most commonly studied psychosocial factor in relation to the health of justice-involved veterans. The majority of studies were randomized controlled trials comparing vocational training to usual care among justice-involved veterans in VHA settings (LePage et al, 2016, 2017; LePage, Lewis, Washington, Davis, & Glasgow, 2013; LePage, Ottomanelli, Barnett, & Njoh, 2014; LePage, Washington, Lewis, Johnson, & Garcia-Rea, 2011). Screening for psychosocial issues in primary care was addressed by two studies (Bikson, McGuire, Blue-Howells, & Seldin-Sommer, 2009; Cook, Freedman, Freedman, Arick, & Miller, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Vocational training was the most commonly studied psychosocial factor in relation to the health of justice-involved veterans. The majority of studies were randomized controlled trials comparing vocational training to usual care among justice-involved veterans in VHA settings (LePage et al, 2016, 2017; LePage, Lewis, Washington, Davis, & Glasgow, 2013; LePage, Ottomanelli, Barnett, & Njoh, 2014; LePage, Washington, Lewis, Johnson, & Garcia-Rea, 2011). Screening for psychosocial issues in primary care was addressed by two studies (Bikson, McGuire, Blue-Howells, & Seldin-Sommer, 2009; Cook, Freedman, Freedman, Arick, & Miller, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…IPS has successfully assisted persons with spinal cord injuries (28,29), mental illness (24,30,31), posttraumatic stress disorder (PTSD; 32), and cognitive impairment (33)(34)(35) to rapidly find employment; however, there has been limited focus on persons with felony convictions. A secondary evaluation of IPS for veterans with spinal cord injuries demonstrated that those who found employment had fewer average arrests and a lower rate of felony convictions (36). In addition, recent work has shown IPS to be more beneficial than a job club in working with individuals with severe mental illness who have legal convictions, misdemeanors, or felonies (37).…”
mentioning
confidence: 99%
“…For example, in a study of individuals with legal histories and severe mental illness, 31% who received supported employment had found employment within a year, compared with 7% of those offered a job club (Bond et al, 2015). In a study of supported employment for veterans with spinal cord injury, employment rates at 12-month follow-up for those with felony histories was 18% in the supported employment condition and 11% in the treatment-as-usual condition (LePage, Ottomanelli, Barnett, & Njoh, 2014). Though these comparisons are useful, it must be acknowledged that vocational outcomes are difficult to compare between studies due to factors such as local unemployment rates, specific barriers of the population, skill sets of the populations studied, and overall safety net of the community.…”
Section: Discussionmentioning
confidence: 99%